2006
DOI: 10.1016/j.fertnstert.2006.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Aging and infertility in women

Abstract: BACKGROUNDFemale fertility begins to decline many years prior to the onset of menopause despite continued regular ovulatory cycles. Although there is no strict definition of advanced reproductive age in women, infertility becomes more pronounced after the age of 35. A classic report on the effect of female age on fertility found that the percentage of women not using contraception who remained childless rose steadily according to their age at marriage: 6% at age 20 to 24, 9% at age 25 to 29, 15% at age 30 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Controls were age matched to within 1 year of the cancer patient, as female age is the greatest prognostic indicator of IVF success [28]. Patients were included over 17 years, during which time technology changes and protocols evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Controls were age matched to within 1 year of the cancer patient, as female age is the greatest prognostic indicator of IVF success [28]. Patients were included over 17 years, during which time technology changes and protocols evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Fertility in women starts declining at age 35 years and decreases more rapidly after age 40 years [[1], [2], [3], [4]], with a dramatically increased incidence of infertility, miscarriage, congenital birth defects and fetal aneuploidy [5,6]. Accumulating evidence has indicated that poor oocyte quality is a common and unmanageable problem for women with advanced maternal age, which leads to the unsuccessful reproductive outcome [[7], [8], [9]]. Age-related quality decrease in the ovary reserve occurs as a result of two processes: increased oxidative damage in oocytes caused by excessive reactive oxygen species (ROS) [[10], [11], [12]] and compromised antioxidant defense systems.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of evidence that IVF is effective in couples without an absolute IVF indication, IVF is often considered as a last resort for all subfertile couples regardless of the etiology of their subfertility [7–12] . Contrary to the perception of many, IVF does not guarantee success; almost 38–49% of couples that start IVF will remain childless, even if they undergo six IVF cycles [13] .…”
Section: Introductionmentioning
confidence: 99%